Impact behaviour of dissimilar AA2024-T351/7075-T651 FSWed butt-joints: effects of Al2O3-SiC particles addition (Fracture and Structural Integrity, 2022)
Dissimilar friction stir welding joints are widely employed in the industrial field due to the excellent microstructural and mechanical properties of the resulting joints. Nevertheless, to further enhance the weld properties, the addition of reinforcement particles on the joint-line during the process has been proven effective for increasing its mechanical performance. In the present investigation, the microstructure and the impact behaviour of FSWed joints between AA2024-T351 and AA7075-T651 aluminium plates were investigated, considering the effect of different process parameters selected through a full factorial 2k design of experiments: both the rotational and translational speed of the tool, as well as the addition of Al2O3-SiC microparticles, were considered as input parameters. Unnotched 10 x 5 x 55 mm impact specimens were tested through an instrumented 50 J Charpy pendulum: total impact energy, the two complementary initiation and propagation energies as well as the peak force were correlated to the adopted process parameters. From the performed analyses, it was found that joints with reinforcing particles are prone to form wormhole defects across the stir zone that not only affect the microstructural development, but also the impact behaviour since they require less energy at break in comparison with joints fabricated without particles addition.
Keywords: Friction stir welding; Impact strength; Dissimilar joints; Particles-reinforcement; Microstructure